THE INFLUENCE OF SUPERVISION AND CONTROL FUNCTIONS ON THE LEVEL OF JOB COMPLETION IN THE SUB-DISTRICT OFFICE BELITANG MADANG RAYA OKU TIMUR - Winda Feriyana; Ripda Erwin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Belitang Madang Raya is a sub-district in the OKU Timur district, in improving work completion the organization continues to strive to carry out supervision and control both internally by the leadership of the organization and externally, so that in a preventive manner the implementation of fraud, errors and omissions can be prevented. Then with this supervision and control, every error or error can be found a solution by conducting guidance and coaching so that employees are expected to minimize mistakes in carrying out work, and this will motivate employees to carry out their duties in accordance with applicable regulations. This study aims to analyze partially and jointly the influence of the supervisory function, work control on the level of work completion and to analyze the most dominant variable in influencing the level of work completion at OKU Timur Belitang Madang Raya District Office, the results of regression analysis and the correlation between the supervisory function of the level of work completion shows the regression model Ŷ = 17.420 + 0.641X1 + e with a correlation coefficient of 0.500. The results of the regression analysis and the correlation between control of the level of work completion show the regression model Ŷ = 21.011 + 0.577X2 + e with a correlation coefficient of 0.707. The results of multiple regression analysis and the correlation between the supervisory and control functions together on the level of work completion show the regression model Ŷ = 1.701 + 0.525X1 + 0.531 X2 + e with a correlation coefficient of 0.815. From the multiple linear regression equation above, it shows that the control function variable (X1) has more dominant influence on the level of work completion than control. This research was conducted on 25 respondents with the analytical method used is path analysis using SPSS software. Keywords : Supervision, Control, Work Completion Rate